2004
DOI: 10.2134/agronj2004.0792
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Disease, Nitrogen Source, and Risk on Optimal Nitrogen Fertilization Timing in Winter Wheat Production

Abstract: the season without significantly affecting yield. Because disease stress can reduce N uptake (Dilz et al., 1982), Nitrogen source and timing can interact with glume blotch (Stago-N timing and fungicide applications should be based on nospora nodorum) and take-all root rot (Gaeumannomyces graminis the characteristics of each wheat crop and environment var. trittici) to affect risk in wheat (Triticum aestivum L.) production.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
10
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 35 publications
2
10
0
Order By: Relevance
“…Some studies have also investigated the effects of technological changes on 1 Econometric studies of production risk in agriculture using a primal model approach include Antle (1983), Antle andGoodger (1984), Di Falco et al (2007), Groom et al (2008), Griffiths and Anderson (1982), Kumbhakar (1993), Just and Pope (1979), Nelson and Preckel (1989), Regev et al (1997), Roberts et al (2004), Serra et al (2006), Traxler et al (1995) Wan and Anderson (1990), and Wan et al (1992), while aquaculture has been studied by Asche and Tveteras (1999) and Tveteras (1999Tveteras ( , 2000. 2 The state contingent approach (Chambers and Quiggin, 2001) has been introduced as an alternative to the traditional parametric stochastic production function approaches such as the Just-Pope specification belongs.…”
Section: Introductionmentioning
confidence: 99%
“…Some studies have also investigated the effects of technological changes on 1 Econometric studies of production risk in agriculture using a primal model approach include Antle (1983), Antle andGoodger (1984), Di Falco et al (2007), Groom et al (2008), Griffiths and Anderson (1982), Kumbhakar (1993), Just and Pope (1979), Nelson and Preckel (1989), Regev et al (1997), Roberts et al (2004), Serra et al (2006), Traxler et al (1995) Wan and Anderson (1990), and Wan et al (1992), while aquaculture has been studied by Asche and Tveteras (1999) and Tveteras (1999Tveteras ( , 2000. 2 The state contingent approach (Chambers and Quiggin, 2001) has been introduced as an alternative to the traditional parametric stochastic production function approaches such as the Just-Pope specification belongs.…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, ear height was also found significantly taller (121 cm) with the application of only 100 kg N ha -1 . The taller ear and plant height might be due to increment in dry matter accumulation as N contributed more for vegetative growth as mentioned by Roberts et al (2004). The result showed a significant effect of N on plant and ear height.…”
Section: Plant and Ear Heightmentioning
confidence: 82%
“…It enhances water use efficiency and hastens crop maturity. This nutrient play important role in photosynthesis, cell division, energy transfer, root growth, cell enlargement, root formation (Roberts, 2004). In the soil Potassium (K) is not readily available; it is involved in the structural component of soil minerals.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Increasing N rates retarded tan spot development [66,69,73,91,92,93,94]. However, Bockus and Davis [95] suggested that N applications do not directly affect tan spot severity, but rather appear to reduce disease impact through delayed leaf senescence or that high N rates increase Septoria leaf blotch or tan spot severity due to an increase in crop biomass production, which creates a microenvironment conducive to fungal development in humid regions [82,84,85,96,97]. In addition, experiments carried out in Argentina indicated that yield increase and increase in yield components due to application of tebuconazole was similar in fertilized and non fertilized conditions, despite the increase in the area under disease progress curve under N fertilization [82].…”
Section: The Use Of Fungicides In the Integrated Foliar Disease Managmentioning
confidence: 99%